In the context of a daycare center: nursing and their representations of child care as an educational act - Sarubbi Jr., Vicente; Muylaert, Camila Junqueira; Gallo, Sophia Motta; Gallo, Paulo Rogério (Revista da Escola de Enfermagem da USP, 2014)
This study aimed to analyze the social representations in the professionals of technical staff, who work with children at USP daycare centers. Eight professionals of the nursing field underwent a semi-structured interview. The interviews were recorded and transcribed in their entirety and the content of the discourse was subjected to thematic-categorical analysis. The categories were transformed into variables and processed by the software Classification Hiérarchique Classificatoire et Cohésitive (CHIC®) and analyzed by the hierarchical similarity tree. The results indicate that actions to promote health are reported as educational and transformative, in which health care gains new meaning through contextualized conceptions in the field of child education. We conclude that professionals attribute new meanings to their practices in the health care environment of daycare centers as their representations shifts from the logic of the biomedical field to a logic of educational care. In this sense, they perceive themselves as being challenged to establish an interaction with the children in terms of their activities related to the promotion of health and in an educational act.